2021
DOI: 10.1039/d1sm00986a
|View full text |Cite
|
Sign up to set email alerts
|

Blistering failure of elastic coatings with applications to corrosion resistance

Abstract: A variety of polymeric surfaces, such as anti-corrosion coatings and polymer-modified asphalts, are prone to blistering when exposed to moisture and air. As water and oxygen diffuse through the material,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Several surface instabilities, such as surface wrinkling, dewetting, , and blistering, have been reported for thin films supported on a solid substrate. Surface wrinkling results in periodic wrinkles, whereas dewetting relieves mesostructures such as holes, droplets, or polygonal networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several surface instabilities, such as surface wrinkling, dewetting, , and blistering, have been reported for thin films supported on a solid substrate. Surface wrinkling results in periodic wrinkles, whereas dewetting relieves mesostructures such as holes, droplets, or polygonal networks.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we discuss if osmotic pressure (π op ) could lead water and solutes to flow into the inner region of a P2VP film. Previous papers have demonstrated that osmotic pressure is a crucial driving force for water flow from low π op to high π op . ,, For example, osmotic blisters can occur for metallic materials with polymer coating when chemical reactions (such as corrosion) occur at the metal–polymer interface. , The chemical reactions form water-soluble components. The water-soluble components act like solutes, producing a higher π op for corrosive metals with polymer coating than for pure water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once corrosion phenomena are initiated, the abundant release of H 2 causes blisters formation. The accumulation of H 2 under polymeric layer makes them grow and ultimately burst with prolonged immersion [ 150 ]. Additionally, polymeric layers are prone to swelling and subsequent delamination in the presence of physiological media [ 151 ].…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…The circular blister can originate from film imperfection or is triggered by indentation or nanoindentation. [147][148][149] When the circular blister grows, its edge will become unstable and form a petal-like pattern, as shown in Fig. 14(a).…”
Section: Combined Cracking and Bucklingmentioning
confidence: 99%